Development and characterization of an anti-bat antisera and its implementation in screening for rabies antibody in bats via ELISA and IFA - Schmidt, Kelsey M., author; Gordy, Paul W., author; Bowen, Richard A., author (Colorado State University. Libraries, 2004)
Bats have long been associated with the transmission of a number of zoonotic agents, including human rabies. Comprehensive surveys of wild bat populations to characterize the seroprevalance rate of the population could prove helpful in implementing control programs designed to reduce the number of human and veterinary cases resulting from bat-associated rabies. The antiserum was developed by immunizing rabbits with purified Eptesicus fuscus (big brown bat) IgG. Following immunization, the rabbits were bled and the anti-bat antiserum was purified and characterized. The antisera is currently being used to develop an indirect enzyme-linked immunosorbent assay (ELISA) and an indirect immunofluorescent antibody test (IFA), which will be used to screen for rabies-specific IgG antibody in bats. While these tests do not detect active viral infection or neutralizing antibody, they have clear advantages over the rapid fluorescent focus inhibition test (RFFIT), fluorescent antibody virus neutralization test (FAVN) and mouse inoculation test. The proposed methods do not require the use of live virus for the assay and are inexpensive. They also confer a clear advantage in that the amount of serum required for the assay is considerably less than that which is required for RFFIT or FAVN. We describe the development of the rabbit anti-bat IgG antibody and report preliminary results on our ELISA and IFA assays.
Keywords: Rabies -- Serodiagnosis; Immune serums; Eptesicus; Bats as carriers of disease